Pengaruh Partisipasi Orang Tua terhadap Motivasi Belajar Siswa Kelas V SDN 023 Pandau Jaya Kabupaten Kampar - Mardiyah, Ainul; Mustika, Dea (Lembaga Yasin AlSys, 2023)
The learning motivation of students at SDN 023 Pandau Jaya, Kampar Regency, is still relatively low because some of the students whose parents participate are not optimal both physically and non-physically. This study aims to determine whether there is an influence of parental participation on the learning motivation of fifth grade students at SDN 023 Pandau Jaya, Kampar Regency. This type of research uses a quantitative approach to the ex-post facto method. The population of this study was 87 students of class V with the sampling technique using the non-probability sampling method, namely saturated sampling. So a sample of 87 students consisted of 46 boys and 41 girls. The data collection technique used a questionnaire and was processed using a correlation test with the help of SPSS Version 24. The results showed that based on the calculation of the research hypothesis that had been carried out, it was found that the value of tcount > ttable (7,580 > 1,980), then Ha was accepted, Ho was rejected. Based on this, it can be concluded that there is an influence between parent participation on the learning motivation of fifth grade students at SDN 023 Pandau Jaya, Kampar Regency.